IMPLEMENTATION OF LOVE-BASED CHARACTER EDUCATION AT AULADUNA IT KINDERGARTEN, BENGKULU - Miza Syahfitri Jana; Emilianti; Sangkut Karunia Dwika; Cheiaka Septa Relita; Mice Sintia; Lifti Putri Ismadiana; Fidhia Andani (STMIK Indonesia Banda Aceh, 2026)
Character education at the Early Childhood Education (PAUD) level is the main foundation in the formation of children's personalities from the golden age . This study aims to describe the implementation of love- based character education at TK IT Auladuna Bengkulu, including the forms of activities , teacher strategies, and supporting and inhibiting factors in its implementation . This study uses a qualitative approach with a descriptive method . Data were collected through observation , interviews with the principal , teachers, and parents , and documentation studies . The research subjects consisted of 2 class teachers , 1 principal , and 15 group B students . The results of the study indicate that love -based character education is implemented through the habituation of compassion , teacher role models , thematic learning with Islamic nuances , and strengthening the values ​​of love for God, others , and the environment . This implementation has been proven to be able to improve children's social-emotional abilities , even though they are still faced with limited facilities and various family backgrounds . This study provides a practical contribution for PAUD teachers in designing love - based learning and theoretical contribution to the development of the concept of character education based on Islamic values ​​in early childhood